2022
DOI: 10.1002/ajhb.23818
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity index is a better predictor to discriminate metabolic syndrome than other classical adiposity indices among young adults

Abstract: Background: Visceral adiposity index (VAI) has been identified as a cardiometabolic risk marker in children and adolescents which reflects abdominal fat distribution. The aim of the present study was to evaluated the predictive capacity of VAI, a body shape index (ABSI), atherogenic index of plasma (AIP), and triglycerides and glucose index (TyG index) compared with classical anthropometric measurements to discriminate metabolic syndrome (MetS). Methods: This retrospective study included 1372 individuals. Anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…compared the predictive power of AIP, non-HDL-c, LDL-c/HDL-c, TG/HDL-c, and TC/HDL-c in discriminating MetS in the Chinese population and revealed that AIP was a better index to identify MetS than the other lipid parameters [ 10 ]. Vega-Cardenas and colleagues found that AIP had a strong predictive ability for MetS (AUC = 0.91), and the optimal cutoff point was 0.44 [ 41 ]. Furthermore, a study conducted among various ethnicities in China showed that AIP has a good predictive performance for MetS, and the cutoff values for AIP ranged from − 0.1 to 0/07 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…compared the predictive power of AIP, non-HDL-c, LDL-c/HDL-c, TG/HDL-c, and TC/HDL-c in discriminating MetS in the Chinese population and revealed that AIP was a better index to identify MetS than the other lipid parameters [ 10 ]. Vega-Cardenas and colleagues found that AIP had a strong predictive ability for MetS (AUC = 0.91), and the optimal cutoff point was 0.44 [ 41 ]. Furthermore, a study conducted among various ethnicities in China showed that AIP has a good predictive performance for MetS, and the cutoff values for AIP ranged from − 0.1 to 0/07 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the studies’ results may be due to differences in participants’ age, ethnicity, and MetS diagnosis criteria. For instance, in our study, IDF criteria were used to define MetS, while American Heart Association (AHA) criteria were used in Vega-Cardenas et al’s study [ 41 ]. The results of logistic regression exhibited a significant association between the AIP and the MetS risk in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…All anthropometric measurements were collected by trained nutritionists in a conditioned/equipped clinic in CAIS. The body adiposity index (BAI) was calculated as BAI = [hip circumference (cm) ÷ height (m) 1.5] − 18 [28], whereas the visceral adiposity index (VAI) was estimated as VAI = (WC (cm)/(39.68 + (1.88 × BMI))) × (triglycerides/1.03) × (1.31/high-density lipoprotein cholesterol or HDL-c) for males and VAI = (WC (cm)/(36.58 + (1.89*BMI))) × (triglycerides/0.81) × (1.52/HDL-c) for females [29]. The BAI is a useful measure of body fat percentage, which can be calculated from the HC and height only, with an accessible application in a clinical setting [28].…”
Section: Anthropometric Measurements and Blood Pressurementioning
confidence: 99%
“…Furthermore, the BAI has been validated in individuals of Mexican ancestry with widely varying adiposity levels [28]. Likewise, the VAI has been identified as a reliable parameter reflecting abdominal fat distribution and a promising tool to identify metabolic syndrome and cardiometabolic risk [29]. This index also uses conventional issues for its calculation, being simple to apply in epidemiological research.…”
Section: Anthropometric Measurements and Blood Pressurementioning
confidence: 99%
“…However, the BMI by itself does not distinguish lean and fat tissues, which explains previous observations that a significant proportion of overweight (~50%) and obese (~30%) individuals do not show any metabolic alterations or health complications [ 5 , 6 ]. Of the components of MetS, HDL-cholesterol [ 7 ] and triglycerides (TG) [ 8 , 9 ] levels have greater predictive power for classifying metabolic health over waist circumference (WC), systolic and diastolic blood pressure (SBP/DBP), and glucose. Therefore, there is a need for a more accurate assessment of metabolic health at the individual level and the categorization of individuals beyond their BMI.…”
Section: Introductionmentioning
confidence: 99%